Kepemimpinan Dan Pendidikan Islam - Nurhayati (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Leadership is a conscious effort undertaken by a person (leader) to be able to realize the objectives of the organization through others by providing motivation so that others will implement it, and therefore it is necessary balance between the individual needs of the executive. A leader must certainly understand and understand the fundamentals of leadership in order to be a leader, whether in small scope, such as family, discussion leaders, etc. as well as leaders in large scope such as leaders oganizations, religious leaders, country leaders and so on. However there are several issue. The education is a process of mentoring, educating that is given intentionally towards students by adults to achieve the goal of the education itself. Islamic education is the establishment of a personality to be a human beings who have the karimah to be in the daily life to get happiness, tranquility, and can reflect the behavior according to the Shari’ah Islam that is sourced in the Qur’an, Sunnah Rasul and Ijtihad. The education leadership is the ability to drive educational implementation to achieve educational objectives. This understanding is in line with the angle of leadership philosophy that in fact uphold the principle of humanity (human relationship).